PENGARUH PENAMBAHAN ARANG BATOK KELAPA TERHADAP KUAT TEKAN MORTAR - Sihombing, Adi Putra; Afrizal, Yuzuar; Gunawan, Agustin (Inersia: Jurnal Teknik Sipil, 2018)
Mortar is a mixture of adhesives (portland and lime cement), sand and water with certain compositions. Use of adhesive materials on building construction in general still use portland cement, but in terms of portland cement costs are required a greater cost. This study aims to determine the behavior of the compressive strength of mortar using Coconut Shell Charcoal (CCS) as a substitute for cement. The method of manufacture and testing of mortar compressive strength refers to SNI 03-6825-2002 with mortar 1Pc: 3Ps mortar. Range of initial flow values used is 105% - 115%. CCS used is pass No. 200 which utilizes combustion results from coconut shells. Variations of mortar test specimens were 0%, 2.5%, 5%, 7.5%, 10% and 12.5% respectively each variation had 10 sample specimens. Test sample was immersed for 27 days and compressive strength mortar test was performed at 28 days. Value compressive strength of mortar on variations of 0%, 2.5%, 5%, 7.5%, 10%, 12.5% are 25.11 MPa, 25.65 MPa, 26.07 MPa,27.00 MPa, 26.40 MPa and 25.98 MPa. The highest increase of mortar compressive value was variation of 7.5% by 7.51%.